(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A variety of natural and/or manmade activities may release dangerous air pollutants or chemicals into the environment, which can have significant health repercussions. Air pollutants such as oxides of nitrogen ( nox, sulfur dioxide (SO2), carbon monoxide (CO), heavy metals, and particulate matter (PM) affect a range of human organs, especially the cardiovascular system. According to the International Agency for Research on Cancer, ambient air pollution causes lung cancer (IARC). In addition, several epidemiological studies have shown a link between air pollution or the risk of lung cancer and mortality. However, only a few research are investigating the molecular effects of air pollution exposure, notably in lung cancer, because to several difficulties in replicating air pollution exposure in basic experiments. Another major issue is the lack of appropriate adjustments for exposure misclassification due to the fact that air pollution changes depending on time, location, and socioeconomic level. The author of this publication discusses the challenges and future prospects of genetic research in lung malignancies induced by air pollution. As a result, the goal of this work is to evaluate current molecular knowledge of air pollution-related lung cancer as well as possible future directions in this difficult but vital research topic.